Talking about the Aboriginal Community: Child Protection Practitioners’ Views - Walmsley, Christopher (First Peoples Child & Family Review, 2004)
Child protection practitioners view Aboriginal communities as victim, adversary, participant, partner, and protector of children. These representations of communities are derived from interview data with 19 Aboriginal and non-Aboriginal child protection social workers in British Columbia, Canada. The representations of the community are informed by the practitioner’s geographic relationship to the community and the length of community residency (including whether it’s the practitioner’s community of origin). Practitioners view communities as a victim or adversary when no relationship of trust exists with the community. Practitioners view communities having a participative or partnership role in child protection when trust has developed. When communities take full responsibility for children’s welfare, practitioners view the community as the protector of children. No clear association was found between the different representations of the community and the practitioner’s culture or organizational auspices. The practitioner’s own vision of practice is believed to signiﬁcantly inﬂuence the relationship that develops with the community.